Silent Circulation of Rift Valley Fever in Humans, Botswana, 2013–2014 - Sanderson, Claire E.; Jori, Ferran; Moolla, Naazneen; Paweska, Janusz T.; Oumer, Nesredin; Alexander, Kathleen A. (Emerging infectious diseases, 2020)
We evaluated the prevalence of Rift Valley fever virus IgG and IgM in human serum samples (n = 1,276) collected in 2013-2014 in northern Botswana. Our findings provide evidence of active circulation of this virus in humans in the absence of clinical disease in this region.